1982
DOI: 10.1042/cs063061s
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane and Renal Function in Relation to Hypertension in Rats of the Milan Hypertensive Strain

Abstract: 1. The aim of this study was to compare certain renal and erythrocyte functions in the Milan hypertensive strain (MHS) of rats and in normotensive control animals (MNS).2. Under experimental conditions close to those in conscious unmanipulated animals, the glomerular filtration rate (GFR) per g kidney weight was higher and the kidney weight/body weight ratio lower in MHS than in MNS rats (P < 0-001). This suggests that there is increased transtubular ion transport in MHS animals.3. The MHS rats had a higher ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 7 publications
2
18
0
Order By: Relevance
“…As already shown in previous papers (17,37), at this age the GFR, relative to kidney weight, was substantially increased in MHS compared with MNS animals; moreover, no significant difference in systemic blood pressure was found between the two strains of rats; i.e., the MHS rats were still in the prehypertensive stage. With respect to plasma osmolality and AVP concentration levels, the results did not show any significant difference between MNS and MHS rats.…”
Section: Resultssupporting
confidence: 60%
“…As already shown in previous papers (17,37), at this age the GFR, relative to kidney weight, was substantially increased in MHS compared with MNS animals; moreover, no significant difference in systemic blood pressure was found between the two strains of rats; i.e., the MHS rats were still in the prehypertensive stage. With respect to plasma osmolality and AVP concentration levels, the results did not show any significant difference between MNS and MHS rats.…”
Section: Resultssupporting
confidence: 60%
“…Moreover, previous experiments on isoiated perfused kidney of MHS and MNS showed that addition af 1 mM ouabain to the perfusate induced a greater natriuretie response in MHS kidney, in keeping with a greater ouabain-sensitive Na* reabsorption [ 161. Taken together, these results fit with the physiological data available on MHS rats, among which the most relevant are a higher whole-kidney glomerular filtration rate (G-FR) [l, 171, a lower kidney weight [1,17], the ability to maintain a normal sodium balance despite the faster GFW [18] and a blunted tubulo-glomerular feedback mechanism [19]. In fact all these data can be explained by a primary increase of proximal tubular reabsorption.…”
Section: Discussionsupporting
confidence: 76%
“…Measurement of GFR by infusing inulin at a rate that produced a plasma concentration ϳ1 mg/ml showed lower values in prehypertensive MHS compared with normotensive control MNS (56). A subsequent measurement performed with a plasma inulin ϳ0.1 mg/ml, disclosed higher GFR in the prehypertensive MHS (58). These contrasting results were obtained with the same experimental procedure except plasma inulin.…”
Section: Personal Approachmentioning
confidence: 41%
“…Several reasons supported these conclusions: a plasma inulin concentration of 1 mg/ml exerts an osmotic force that may produce different cellular reactions; according to the genetic network (58), only a higher GFR is consistent with 1) the findings in isolated MHS and MNS kidneys (121,122); 2) a constitutive increase in renal Na reabsorption (as it occurs in other contexts, i.e., mineralcorticoid administration), either measured in the whole kidneys (121,122) or inferred from the Na transport measurements across the cell membranes removed from MHS and MNS kidneys (52,53,72); 3) a mild and transient renal Na retention during development of hypertension (15). Also in humans, GFR may be higher or lower in offspring of hypertensive parents compared with offspring of normotensive parents (17,46,145).…”
Section: Personal Approachmentioning
confidence: 79%